A cross-linking/mass spectrometry workflow based on MS-cleavable cross-linkers and the MeroX software for studying protein structures and protein–protein interactions. Issue 12 (December 2018) - Iacobucci, Claudio; Götze, Michael; Ihling, Christian; Piotrowski, Christine; Arlt, Christian; Schäfer, Mathias; Hage, Christoph; Schmidt, Rico; Sinz, Andrea
Abstract Chemical cross-linking in combination with mass spectrometric analysis of the created cross-linked products is an emerging technology aimed at deriving valuable structural information from proteins and protein complexes. The goal of our protocol is to obtain distance constraints for structure determination of proteins and to investigate protein–protein interactions. We present an integrated workflow for cross-linking/mass spectrometry (MS) based on protein cross-linking with MS-cleavable reagents, followed by enzymatic digestion, enrichment of cross-linked peptides by strong cation-exchange chromatography (SCX), and LC/MS/MS analysis. To exploit the full potential of MS-cleavable cross-linkers, we developed an updated version of the freely available MeroX software for automated data analysis. The commercially available, MS-cleavable cross-linkers (DSBU and CDI) used herein possess different lengths and react with amine as well as hydroxy groups. Owing to the formation of two characteristic 26-u doublets in their MS/MS spectra, many fewer false positives are found than when using classic, non-cleavable cross-linkers. The protocol, exemplified herein for BSA and the wholeEscherichia coli ribosome, is robust and widely applicable, and it allows facile identification of cross-links for deriving spatial constraints from purified proteins and protein complexes. The cross-linking/MS procedure takes 2–3 days to complete. Valuable structural information can be derived by chemical cross-linking of proteins followed by mass spectrometry of the products. Iacobucci et al. use MS-cleavable reagents, enrichment by strong-cation-exchange chromatography, and LC-MS/MS analysis.